Approach to comprehensive website testing: combining usability and functional test methods - Vovk, O. V.; Chebotarova, I. B.; Mendielieva, M. V. (ТОВ «Друкарня Мадрид», 2025)
Testing website interface is a rather complicated process due to the large variety of existing testing methods. The article discusses an approach for testing the interfaces of educational and e-commerce websites in working conditions, which includes a combination of usability and functional testing methods. Based on the analysis of test results, possible types of websites projects and their constraints, we propose a test approach that provides an effective usability evaluation and verification of interface interaction with the server-side component of educational or e-commerce website. We expect the proposed approach can be used to identify a larger number of errors on a website in use and to form recommendations for its improvement when testing resources are limited.
Keywords: website; USABILITY